2007
DOI: 10.1523/jneurosci.1051-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing Neurons with Carbon Nanotubes: Electrical Signal Transfer and Synaptic Stimulation in Cultured Brain Circuits

Abstract: The unique properties of single-wall carbon nanotubes (SWNTs) and the application of nanotechnology to the nervous system may have a tremendous impact in the future developments of microsystems for neural prosthetics as well as immediate benefits for basic research. Despite increasing interest in neuroscience nanotechnologies, little is known about the electrical interactions between nanomaterials and neurons. We developed an integrated SWNT-neuron system to test whether electrical stimulation delivered via SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
257
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(276 citation statements)
references
References 26 publications
10
257
0
7
Order By: Relevance
“…Carbon nanotube platforms have also been shown to support network connectivity and synaptic plasticity in mammalian cortical circuits 43 . Carbon nanotube-neuron hybrid networks have been shown to detect a boost in signal transmission with increase in frequency of synaptic events 51,52 . Single-cell activity of an individual neuron has been shown to be affected when they interact with a carbon nanotube substrate 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Carbon nanotube platforms have also been shown to support network connectivity and synaptic plasticity in mammalian cortical circuits 43 . Carbon nanotube-neuron hybrid networks have been shown to detect a boost in signal transmission with increase in frequency of synaptic events 51,52 . Single-cell activity of an individual neuron has been shown to be affected when they interact with a carbon nanotube substrate 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Later, we further demonstrated that, in a similar fashion, SWCNTs interfaced to neurons are equally able to induce a potentiation of spontaneous synaptic activity in cultured hippocampal networks. 29 This increase in spontaneous activity of cultured brain circuits was not due to the building up of networks of different sizes with respect to control growth supports, as the neuronal density (quantified by immunocytochemistry experiments) was similar in the two culturing conditions, as well as the cell body size and the number of neurites emerging from the soma. 28,29 The control and neurons grown on CNTs also showed similar membrane passive properties (input resistance, capacitance, and resting potential), again indicating similar cellular dimensions and healthy state in both culturing conditions.…”
Section: ■ Scaffolds For Nerve Tissue Engineering and Carbon Nanotubesmentioning
confidence: 84%
“…Neurons and electrically excitable cells have been successfully recorded from and stimulated via CNT substrates. CNT-neuronal interaction has resulted in enhanced efficiency in signal transmission (Mazzatenta et al, 2007), efficient stimulation (Gheith et al, 2006;Liopo et al, 2006;Lovat et al, 2005) , and recordings with high SNR (Keefer et al, 2008).…”
Section: Charge Delivery and Electrical Stabilitymentioning
confidence: 99%
“…CNT-neuronal interaction has resulted in increased efficiency for signal transmission (Mazzatenta et al, 2007), efficient stimulation (Gheith et al, 2006;Liopo et al, 2006;Lovat et al, 2005), and recordings with high signal-tonoise ratio (SNR) (Keefer et al, 2008Sauter-Starace et al 2009). SWCNTs were the first CNTs tested for electrical stimulation of neurons .…”
Section: Stimulation and Recording In Vitro Via Cnt Substratesmentioning
confidence: 99%